2017
DOI: 10.1080/09553002.2017.1294772
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative changes in the protein and miRNA cargo of plasma exosome-like vesicles after exposure to ionizing radiation

Abstract: This study provides evidence that radiation-induced changes occur in the protein and miRNA cargo of plasma ELVs. These data imply a novel systemic communication pathway between irradiated and non-irradiated cells and tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 74 publications
3
47
0
Order By: Relevance
“…Previous reports have demonstrated that exosomes from irradiated cells can trigger apoptosis in unirradiated cells, an effect known as the bystander effect [39,40], and that hypoxic exosomes can upregulate angiogenesis [41,42]. However, our study further shows that exosome uptake by hypoxic cancer cells can be modulated by exposing the cells producing the exosomes to hypoxia and/or ionizing radiation.…”
Section: Discussionmentioning
confidence: 41%
“…Previous reports have demonstrated that exosomes from irradiated cells can trigger apoptosis in unirradiated cells, an effect known as the bystander effect [39,40], and that hypoxic exosomes can upregulate angiogenesis [41,42]. However, our study further shows that exosome uptake by hypoxic cancer cells can be modulated by exposing the cells producing the exosomes to hypoxia and/or ionizing radiation.…”
Section: Discussionmentioning
confidence: 41%
“…It is revealed that some miRs with elevated expression during VC promote osteogenesis via targeting at anti‐calcification proteins or contractile markers, whereas some other miRs with decreased expression suppress osteogenesis of VSMCs through targeting at osteogenic transcription factors (shown in Table ). As described, some of such miRs, including miR‐133b, miR‐204, miR‐211, alter during VC and are also proven to be transported by exosomes to modulate the biological behaviour in various kinds of recipient cells . Such results indicated that exosomes could participate in VC through transporting miRs to influence phenotype transition.…”
Section: Exosomes Participate In Vcmentioning
confidence: 73%
“…A major mechanism of radioresistance in cancer cells is altered expression of DDR components and DNA repair pathway such as NHEJ or homologous recombination (HR). Numerous studies have shown that miRNA expression changes in response to DNA damage in order to regulate DDR and DNA repair pathways [29,33,67]. To identify the impact of miRNAs on DNA repair and radioresistance, Hatano et al transfected 810 different miRNA mimics separately into LNCaP-MLuc cells and then irradiated the miR-transfected cells with 4 Gy dose [55].…”
Section: Mirnas In Response To Radiotherapymentioning
confidence: 99%